Information System of Student Affairs at STMIK Pringsewu Based on Web Mobile - Sri Ipnuwati; Riza Imam As’ari; Sri Surya Mandala (bit-Tech, 2020)
Student affairs are part of the higher education system including and covering the process of planning, organizing, processing and developing student interest in talents, improving student welfare and other supports. Student Affairs are an intra-campus student organization which is an executive institution at the university level, the field of student affairs is also a place for student aspirations in submitting complaints, suggestions, to improve campus progress in the student or academic fields. Information is a message (sound or expression) or a collection of messages consisting of the following items in sequence, symbols or meanings that can be explained from a message or a group of messages. This website is a collection of pages on the internet created in the following way: Specific purpose, and can be interrelated and widely accessed through this page by visiting the home page (home page) using a browser from the website URL